Cost-effectiveness of antihypertensives: A major factor for clinical decision making - Paudel, Sabita; Adhikari, Sudeshana (Journal of Gandaki Medical College-Nepal, 2024)
The cost study of antihypertensive therapy is essential because hypertension is one of the major chronic illnesses causing economic burden to the patients. The expense associated with chronic illnesses like hypertension raises concerns because patients often need long-term medication, often requiring multiple drugs simultaneously. The cost-effectiveness analyses of antihypertensive medications are necessary to determine the most economical treatment options. Since protocols and circumstances vary across settings, such analyses must be conducted to ensure applicability in diverse scenarios.